Ettore Sottsass e l’allestimento come spazio intimo. Mostre d’arte e design (1947-1992) - Trincherini, Elisabetta; Turrini, Davide (Opus Incertum, 2024)
Exhibition design represents an important and integral chapter of Ettore Sottsass jr.’s design activity, spanning from the early stages of his professional journey to the later years, when he headed the eponymous Sottsass Associati studio. This is an aspect of the multifaceted personality of the artist and designer that is still understudied today, yet it reveals an original interpretation of the rules of display, as well as a deep sensitivity towards the works of art and design to be exhibited. From the earliest experiments to the more mature ones, Sottsass approached exhibition design as a cohesive philosophy. His methodology was thoughtful and consistent, with specific features both in terms of distribution and construction, and with regard to the creation of a peculiar and intimate ‘sensory atmosphere’.